KETAHANAN KELUARGA DAN PROSES SOSIALISASI MELALUI RUMAH PERLINDUNGAN SOSIAL ANAK (RPSA) KABUPATEN PADANG PARIAMAN - Walan Yudhiani; Cheri Aulia; Zainal Zainal (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2020)
This paper aims to explore the socialization process of family resilience carried out by the Children's Social Protection House (RPSA) in Padang Pariaman Regency. The family is the first social institution to carry out the socialization process for an individual about love, religious morals, socio-cultural institutions and so on. However, there are still families with social disorganization. As a social institution engaged in the world of children, the RPSA tries to carry out socialization so that family resilience can be realized and neglected children are not found, lack parental attention so that they fall into immoral acts. This research is a field research with a qualitative approach. Data were collected by observing the implementation of the socialization process for family resilience through the Children's Social Protection House (RPSA), in-depth interviews with RPSA administrators, and several parents of children who were in legal problems, and documentation studies. Data analysis was performed by using reduction, display and lever techniques (drawing conclusions). The results of this study are about the socialization process carried out by the Children's Social Protection House (RPSA) in Padang Pariaman district to achieve family resilience so that there are no more neglected children who do not get parental attention so that they fall into immoral acts by providing assistance, protection and education especially for disorganized families of problem children